EXAMINING PROFIT GROWTH DRIVERS IN BALI’S VILLAGE CREDIT INSTITUTIONS WITH LEVERAGE AS MODERATOR - Putu Ayu Anggya Agustina; I Made Ryan Ananta; Elisabeth Ria Viana Praningtyas; I Kadek Bagiana (Kajian Akuntansi, 2026)
This study investigates how the Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), and Non-Performing Loans (NPL) affect profit growth in Badung Regency's Village Credit Institutions (LPDs), utilizing financial leverage (DER) as a moderating variable. Using a quantitative approach, the dataset comprised 918 observation-years from 102 LPDs (2016–2024), analyzed via Moderated Regression Analysis. Findings reveal CAR, NIM, and NPL significantly enhance institutional profit growth. Interestingly, the positive impact of NPL indicates a unique cultural anomaly where strong communal norms supersede standard credit risk theories. Furthermore, financial leverage acts as a strategic amplifier, strengthening the impact of these key financial drivers on institutional earnings. The study is limited by its single-regency focus and the lack of quantitative cultural measurements. Theoretically, this research bridges conventional Agency and Stewardship theories with indigenous Balinese Wrddhi Griya values, offering a unique framework to understand how culturally embedded microfinance institutions balance economic expansion with social accountability.